Teachers’ Subjective Happiness: Testing the Importance of Emotional Intelligence Facets Beyond Perceived Stress - Mérida-López S; Quintana-Orts C; Rey L; Extremera N (Psychology Research and Behavior Management, 2022)
Sergio Mérida-López,1 Cirenia Quintana-Orts,2 Lourdes Rey,3 Natalio Extremera1 1Department of Social Psychology, Social Work, Social Anthropology and East Asian Studies at the University of Malaga, Málaga, Spain; 2Department of Developmental and Educational Psychology at the University of Seville, Seville, Spain; 3Department of Personality, Evaluation and Psychological Treatment at the University of Malaga, Málaga, SpainCorrespondence: Sergio Mérida-López, Department of Social Psychology, Social Work, Social Anthropology and East Asian Studies at the University of Malaga, Málaga, Spain, Tel +34 952137570, Email sergioml@uma.esPurpose: Emotional intelligence (EI) is typically linked to higher subjective happiness scores in human service professionals. It is unknown which EI facets are more predictive in explaining subjective happiness beyond that accounted for by other key predictors such as perceived stress. This study investigated which EI facets were the most predictive in explaining subjective happiness above perceived stress in a relatively large sample of Spanish teachers.Methods: The sample was composed of 1323 Spanish teaching professionals (821 females and 529 secondary school teachers) from different educational centers located in Southern Spain. A student-recruited sampling technique was used, and the surveys included the Wong and Law Emotional Intelligence Scale, the Subjective Happiness Scale, and the Perceived Stress Scale. Predictive and incremental validity was assessed with SPSS, and hierarchical regression analysis was used to predict subjective happiness from EI facets beyond that accounted for by perceived stress.Results: The results showed that all four EI facets correlated significantly with each other. Also, they all were positively and significantly associated with subjective happiness, whereas perceived stress was negatively associated with happiness scores. Moreover, self-emotion appraisal, use of emotions and regulation of emotions accounted for a significant amount of variance in the prediction of satisfaction with life beyond the effects of sociodemographic variables and perceived stress.Conclusion: This study extends the specific contribution of EI facets in predicting subjective happiness, rather than EI as a unified construct, in a relatively large sample of Spanish teachers. Self-focused dimensions involving appraisal, use and regulation of emotions appeared to be the most important predictors of happiness beyond stress experienced by teachers. Improved knowledge of the link between specific dimensions of EI and global subjective happiness might improve training in a well-being prevention program for professional development.Keywords: emotional intelligence facets, perceived stress, happiness, teachers